Assessing the Effectiveness of the Industry-Class Program in the Culinary Department - Afisal, Rendi; Yudana, I Made; Agung, Anak Agung Gede (Indonesian Journal of Educational Research and Technology, 2026)
This study aims to evaluate the implementation of the industry-class program for culinary students at SMK Negeri 3 Denpasar, which has adopted the Merdeka curriculum and the industry-class system since 2017. The research employs a management-based program evaluation approach using the CIPP model (Context, Input, Process, Product). It analyzes the effectiveness of the industry-class program at the school. The research population consists of 113 culinary industry-class students, 14 culinary teachers, and 5 industry partners. The sampling technique used is total sampling, in which the entire population is included as the sample. The evaluation results indicate that the variables of Context, Process, and Product are effective, while the Input variable is ineffective. Overall, the evaluation outcome shows a pattern of (+ - + +), meaning that although the industry-class program at SMK Negeri 3 Denpasar is effective in several aspects, challenges remain in the Input variable that must be addressed to improve the program’s success. The study recommends strengthening resource readiness, improving regulations, and enhancing collaboration with industry partners to optimize program outcomes.